2020
DOI: 10.1002/slct.201903965
|View full text |Cite
|
Sign up to set email alerts
|

Chloroacetyl‐Mediated Modification of Chitosan by Tannic Acid to Synthesize Economical Tanninate‐Chitosan and Its Use in Fluoride Ions Adsorption from Aqueous Solution

Abstract: The multi‐functional, green and environmental acceptable adsorbents were synthesized from activated chitosan for fluoride ions via mild‐strategies. Chloroacetylation reaction was performed to integrate an active group to the chitosan structural unit. Subsequently, the integrated active group was derivatized with tannin acid, an environmental‐friendly natural polyphenol via a simple reaction. The synthesized products were evaluated for their structures via FTIR, 1H‐NMR, UV, SEM‐EDS, elemental mapping, BET surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The band appeared at 564, 711, and 1174 cm −1 corresponds to out‐of‐plane CN bending, out‐of‐plane bending NH, CNC stretching, and so forth. The significant peak noticed at 1586 cm −1 ascribed the bonding vibration of NH in amide II 42,43 . The split peaks at 1645 and 1617 cm −1 represented the CN stretching of acetyl group of amide I ‐‐ 36,44 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The band appeared at 564, 711, and 1174 cm −1 corresponds to out‐of‐plane CN bending, out‐of‐plane bending NH, CNC stretching, and so forth. The significant peak noticed at 1586 cm −1 ascribed the bonding vibration of NH in amide II 42,43 . The split peaks at 1645 and 1617 cm −1 represented the CN stretching of acetyl group of amide I ‐‐ 36,44 .…”
Section: Resultsmentioning
confidence: 97%
“…The significant peak noticed at 1586 cm À1 ascribed the bonding vibration of N H in amide II. 42,43 The split peaks at 1645 and 1617 cm À1 represented the C N stretching of acetyl group of amide I --. 36,44 Disappearance of peak in modified membrane 1645 cm À1 , which is appearing in virgin membrane indicated that C N was used form the bridge with chitosan tannic acid assembly.…”
Section: Fourier Transform Infrared Spectroscopy Analysis (Ftir)mentioning
confidence: 99%
“…Very recently, the Chauhan group 61 developed a method for the fabrication of a tannate–chitosan composite via a chloroacetylation reaction (Fig. 4(b)).…”
Section: Design Of Tannin-immobilized Composites Using Various Substr...mentioning
confidence: 99%
“…117 Moreover, tannin-immobilized composites were used to remediate other contaminants. Sen and co-authors 61 synthesized a tanninate-chitosan composite for the adsorption of fluoride ions from an aqueous solution, which showed a maximum adsorption capacity of 28.57 mg g À1 . Tanninimmobilized composites were used as potential adsorbents for removing methylene blue (MB), 84,215,223 Congo Red, 314 methyl orange, and rhodamine B 148 dyes.…”
Section: Applications In Other Fieldsmentioning
confidence: 99%
“…Both fluoride and arsenic are naturally occurring elements that can be found in groundwater due to geological processes or human activities. So far, millions people in many countries including India, China, USA, Pakistan and Bangladesh have been severely affected by presence of fluoride and arsenate in high concentrations in drinking water [7–12] . The concentration of As(V) and F − in groundwater in some regions far exceed the maximum concentration limits set by the World Health Organization (WHO), indicating the severity of the problem.…”
Section: Introductionmentioning
confidence: 99%